Solid Waste Management in Urban India: Imperatives for Improvement - SINGH, Dr. MAUKAM (The journal of contemporary issues in business and government, 2019)
Existing solid waste collection, transport and disposal systems are mired in turmoil across India. In cities where fast-growing populations produce more and more solid garbage than urban local bodies (ULBs) are unable to efficiently handle, the issue is more severe. Unfair solid waste management presents environmental and public health concerns. This study examines the status of solid waste management in India and recommends that many problems be solved.